Strategi Diferensiasi LKPD oleh Guru di Kelas Heterogen SLB-B YPPALB Kota Magelang - Nur Laila Putri Mardiana; Fadhilah Rahmawati; Aprilia Nurul Chasanah (Dinasti Research, 2026)
Teachers at SLB-B face challenges in serving students with diverse characteristics due to limited time, understanding, and learning resources; consequently, the use of standardized worksheets has not been able to meet individual learning needs and has resulted in suboptimal learning outcomes for students with different disabilities. This study aims to describe the worksheet differentiation strategies implemented by teachers in addressing student heterogeneity of students at SLB-B YPPALB Kota Magelang. The study employs a descriptive qualitative approach with subjects including an 11th grade teacher and three students with autism, non-verbal communication, and speech-hearing impairments. Data were collected through interviews, observations, and documentation. Data validity was achieved through tringulation techniques. The findings revealed that teachers implemented three forms of differentiation: content differentiation through variations in presentation formats and material difficulty levels; process differentiation through individual support, repeated instructions, and the use of concrete and visual media’ and product differentiation through variations in the forms of student work products based on students’ abilities. Students with autism receive differentiated instruction through the provision of high-complexity content and encouragement of more independent learning. Deaf students receive instruction focused on simplifying materials, intensive support, and fine motor skill training. Meanwhile, for students with speech and hearing impairments, differentiation in implementes thorugh visual aids and a more structured learning process. The learning products produced by each student demonstrate adjustments made to their abilities, needs, and learning characteristics. The implementation of these strategies has proven to create a more inclusive and adaptive learning environment that fosters student independence at SLB-B